Analysis of the utilization of leisure time in economic activities of middle school age population in East Luwu Regency - Indrawati Sinur; Madris Madris; Retno Fitrianti (Institute of Computer Science (IOCS), 2023)
Utilization of leisure time is the time allocated by the middle school age population in carrying out economic activities. However, this is actually a concern because it involves human capital investment in the long term which has implications for low income and the inability to support their lives going forward. This study aims to determine some of the conditions that influence school-age residents to choose to use their leisure time to work in carrying out economic activities to meet their daily needs. Among them, household income, wages, school status and child status. The method used in this research is multiple linear regression analysis using primary data sourced from distributing questionnaires in East Luwu Regency. The data was processed using IBM SPSS Statistics 23 software. The results showed that household income had a negative effect on the use of leisure time, wages had a positive effect on the use of leisure time, there was no difference in the status of school children and children who did not go to school on the use of leisure time, and there were differences in status. children who have complete parents and do not have complete parents regarding the use of leisure time in the economic activities of middle school age residents in East Luwu Regency.